2016
DOI: 10.1002/ange.201602066
|View full text |Cite
|
Sign up to set email alerts
|

HfMnSb2: A Metal‐Ordered NiAs‐type Pnictide with a Conical Spin Order

Abstract: The NiAs-type structure is one of the most common structures in solids,but metal order has been almost exclusively limited to chalcogenides.The synthesis of HfMnSb 2 is reported with an ovel metal-ordered NiAs-type structure.H fMnSb 2 undergoes ac onical spin order below 270 K, in marked contrast to conventional magnetic order observed in NiAs-type pnictides.Weargue that the layered arrangement of Hf and Mn makes it aquasi 2D magnet, where the Mn layers with localized magnetic moments (Mn 2+ ;S= 5/2) can inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
3
1
Order By: Relevance
“…Experimentally, it was shown that the wave-vector of the conical spin structure is q z = 0.14. 11,12) The most stable wave vector in our calculations is larger compared with the experimentally measured value.…”
Section: Resultscontrasting
confidence: 56%
See 3 more Smart Citations
“…Experimentally, it was shown that the wave-vector of the conical spin structure is q z = 0.14. 11,12) The most stable wave vector in our calculations is larger compared with the experimentally measured value.…”
Section: Resultscontrasting
confidence: 56%
“…However, the energy difference between that of θ = 90°and θ = 75°is small. It is noted that Murakami et al 11) experimentally showed that HfMnSb 2 has a conical spinstructure in which the spin angle θ is approximately 75°at low temperature. Additionally, from Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations